Comparison of capital structure, risk, and profitability between Islamic and conventional banks in Indonesia - Lubis, Arowadi; Fatmayuni, Ida Ayu; Endraswati, Hikmah (Priviet Social Sciences Journal, 2025)
This study aims to compare Islamic and Conventional Banks in Indonesia in terms of Capital Structure, Profitability, and Risk handling. Data for the analysis were taken from the quarterly financial reports of nine Islamic and Conventional Banks for the 2013Q1 – 2020Q3 period. Binary logistic regression was employed as an analysis tool using SPSS 19 software. The results show that Islamic and Conventional Banks are significantly different in terms of capital structure, profitability, and risk handling. Conventional banks have better capital structures and profitability. Islamic Banks, on the other hand, have better risk management.